The pancreas of the schilbeid catfish, Clupisoma garua (Hamilton, 1822): A histological and histochemical study - Ghosh, Saroj Kumar (Our Nature, 2025)
The objective of this study was to elucidate the cellular architecture of the pancreas in Clupisoma garua, a carnivorous river catfish, using light microscopy techniques. The pancreas was diffused in nature, structurally organized into two main components: exocrine serous acini, which produce digestive enzymes and the endocrine islets of Langerhans, which secrete peptide hormones. The pancreatic islets were scattered throughout the organ, each bounded by a thick connective tissue capsule and surrounded by blood capillaries, demonstrating the rich vascularity of the islets. The alpha, beta and delta cells of the islets were identified by their distinct architecture, positions and varying staining intensities. Zymogenic granules of the exocrine acinar cells exhibited an intense tryptophan reaction, reflecting the precursor of numerous pancreatic enzymes related to the fish's feeding habits. The pancreas played a dual physiological role, functioning both as an exocrine organ, with acinar cells responsible for digestion and as an endocrine organ, with islet tissues regulating glucose homeostasis and other vital physiological processes.